Reconnecting plants and pollinators: challenges in the restoration of pollination mutualisms - Menz, Myles H.M. (2011)
Ecological restoration of plant–pollinator interactions has received surprisingly little attention, despite animal-mediated pollination underpinning reproduction of the majority of higher plants. Here, we offer a conceptual and practical framework for the ecological restoration of pollination mutualisms. Through the use of targeted restoration plantings to attract and sustain pollinators and increased knowledge of the ecological requirements of pollinators,wepropose that pollination could be successfully restored in degraded ecosystems. The challenge for pollination biologists is to integrate their findings with those of plant restoration ecologists to ensure sustainable pollination in restored ecosystems.